Comparison of Intraoperative 3-Dimensional Fluoroscopy With Standard Computed Tomography for Stereotactic Frame Registration. Issue 6 (4th October 2019) - Peng, Terrance; Kramer, Daniel R; Lee, Morgan B; Barbaro, Michael F; Ding, Li; Liu, Charles Y; Kellis, Spencer; Lee, Brian
Abstract: BACKGROUND: Three-dimensional fluoroscopy via the O-arm (Medtronic, Dublin, Ireland) has been validated for intraoperative confirmation of successful lead placement in stereotactic electrode implantation. However, its role in registration and targeting has not yet been studied. After frame placement, many stereotactic neurosurgeons obtain a computed tomography (CT) scan and merge it with a preoperative magnetic resonance imaging (MRI) scan to generate planning coordinates; potential disadvantages of this practice include increased procedure time and limited scanner availability. OBJECTIVE: To evaluate whether the second-generation O-arm (O2) can be used in lieu of a traditional CT scan to obtain accurate frame-registration scans. METHODS: In 7 patients, a postframe placement CT scan was merged with preoperative MRI and used to generate lead implantation coordinates. After implantation, the fiducial box was again placed on the patient to obtain an O2 confirmation scan. Vector, scalar, and Euclidean differences between analogous X, Y, and Z coordinates from fused O2/MRI and CT/MRI scans were calculated for 33 electrode target coordinates across 7 patients. RESULTS: Marginal means of difference for vector (X = −0.079 ± 0.099 mm; Y = −0.076 ± 0.134 mm; Z = −0.267 ± 0.318 mm), scalar (X = −0.146 ± 0.160 mm; Y = −0.306 ± 0.106 mm; Z = 0.339 ± 0.407 mm), and Euclidean differences (0.886 ± 0.190 mm) remained within the predefined equivalence margin differences of −2 mm and 2 mm. CONCLUSION: This study demonstrates that O2 may emerge as a viable alternative to the traditional CT scanner for generating planning coordinates. Adopting the O2 as a perioperative tool may offer reduced transport risks, decreased anesthesia time, and greater surgical efficiency.